2011
DOI: 10.1152/physiolgenomics.00035.2011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the endothelial response to diabetes reveals a role for galectin-3

Abstract: Darrow AL, Shohet RV, Maresh JG. Transcriptional analysis of the endothelial response to diabetes reveals a role for galectin-3. Physiol Genomics 43: 1144 -1152, 2011. First published July 26, 2011 doi:10.1152/physiolgenomics.00035.2011.-To characterize the endothelial dysfunction associated with Type II diabetes, we surveyed transcriptional responses in the vascular endothelia of mice receiving a diabetogenic, high-fat diet. Tie2-GFP mice were fed a diet containing 60% fat calories (HFD); controls were litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…Current research indicates that LGALS3 is upregulated at the mRNA and protein level in unstable plaque regions of carotid endarterectomy specimens, compared with stable regions from the same patients (64). Furthermore, in a recent microarray study, the LGALS3 transcript was found to be upregulated in endothelial cells isolated from obese mice fed a high-fat diet (22). Similarly, LGALS3 is highly expressed in aortic samples from ApoEϪ/Ϫ mice on a high-fat diet and .…”
Section: Discussionmentioning
confidence: 97%
“…Current research indicates that LGALS3 is upregulated at the mRNA and protein level in unstable plaque regions of carotid endarterectomy specimens, compared with stable regions from the same patients (64). Furthermore, in a recent microarray study, the LGALS3 transcript was found to be upregulated in endothelial cells isolated from obese mice fed a high-fat diet (22). Similarly, LGALS3 is highly expressed in aortic samples from ApoEϪ/Ϫ mice on a high-fat diet and .…”
Section: Discussionmentioning
confidence: 97%
“…A study in mice with high-fat diet induced diabetes, it was shown a transcriptional upregulation of galectin-3/AGE-Receptör3 in the endothelial cells [14]. Since galectin-3 is a component of AGE-receptor complex expressed on the surface of renal cells including endothelial cells, galectin-3 upregulation could be involved in diabetic nephropathy development.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, since secreted galectins bind back to glycoproteins on the plasma membrane, as well as to glycans on extracellular matrix glycoproteins, galectins can be highly concentrated at the cell surface. Thus, the galectin-1 concentration used in these studies may reflect the physiologic concentration of galectin-1 encountered by a virus at the endothelial cell membrane (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%